2000
DOI: 10.1063/1.372514
|View full text |Cite
|
Sign up to set email alerts
|

Growth and magnetic properties of thin epitaxial NixPd1−x alloy films on Cu3Au(100)

Abstract: Articles you may be interested inInfluence of stoichiometry and growth temperature on the crystal structure and magnetic properties of epitaxial L10 Fe-Pd (001) films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
(14 reference statements)
2
9
1
Order By: Relevance
“…Compared with the similar studies from other groups, Seider et al [21] observed only four oscillations, but Braun et al [22] observed more than 10 oscillations in their system. In our study, the incident angle is another important factor that has great influence on the MEED oscillation.…”
Section: Meed Oscillationcontrasting
confidence: 52%
See 1 more Smart Citation
“…Compared with the similar studies from other groups, Seider et al [21] observed only four oscillations, but Braun et al [22] observed more than 10 oscillations in their system. In our study, the incident angle is another important factor that has great influence on the MEED oscillation.…”
Section: Meed Oscillationcontrasting
confidence: 52%
“…In this work, Co x Ni 1Àx /Cu 3 Au(1 0 0) with x < 11% is prepared at room temperature. The substrate Cu(1 0 0) (a = 3.61 A ˚) [3,8] is replaced by Cu 3 Au(1 0 0) (a = 3.75 A ˚) [21] in order to get the more obvious strain relaxation. The small concentration of Co can provide another point of view for the SRT studying.…”
Section: Introductionmentioning
confidence: 99%
“…Pronounced intensity oscillations of a diffracted electron beam recorded during film growth indicated a good layer-by-layer growth for Ni 0.35 Pd 0.65 on Cu 3 Au͑100͒ that deteriorates for higher or lower Ni concentrations. 7 A rough surface contributes to breaking the momentum conservation in the photoemission process and leads to a smearing of the photoelectron spectra. The second complication stems from the unknown segregation effect at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic anisotropy is one of the intensively studied issues due to its critical role in magnetic recording. It is known to be affected by several factors, such as structure [1,2], film strain [3] and thickness [4], temperature [5], broken symmetry at the interface [6] and so forth. As a potential candidate for magnetic recording, Ni x Pd 1Àx alloy has been studied for a long time.…”
mentioning
confidence: 99%